النقاط الصامدة العشوائية المشتركة لمؤث ا رت عشوائية إبداليه - جا ا رلله عجيل, Yusra (مجلة كلية التربية, 2020)
In this paper ,we prove three common random fixed point theorems for commuting operators h-nonexpansive and continuous operators defined on a non-starshaped subset of a p-normed space ????. Also hypotheses conclude compactness condition , demi-closeness or Opial condition. Keywords: p-normed spaces , common random fixed point, random best approximation.